Jacques Rancière History, Politics, Aesthetics - Rockhill, Gilbert; Watts, Phillip (Duke University Press, 2009)
The French philosopher Jacques Rancière has influenced disciplines from history and philosophy to political theory, literature, art history, and film studies. His research into nineteenth-century workers' archives, reflections on political equality, critique of the traditional division between intellectual and manual labor, and analysis of the place of literature, film, and art in modern society have all constituted major contributions to contemporary thought. In this collection, leading scholars in the fields of philosophy, literary theory, and cultural criticism engage Rancière's work, illuminating its originality, breadth, and rigor, as well as its place in current debates. They also explore the relationships between Rancière and the various authors and artists he has analyzed, ranging from Plato and Aristotle to Flaubert, Rossellini, Auerbach, Bourdieu, and Deleuze.